2003
DOI: 10.1177/147323000303100512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Haemodynamic Effects of Interscalene Block Combined with General Anaesthesia and Interscalene Block Alone for Shoulder Surgery

Abstract: Interscalene brachial plexus block (ISB) anaesthesia is widely used with or without general anaesthesia in patients undergoing shoulder surgery, which is generally done with the patient in a sitting position. This position affects haemodynamics, and supplementing ISB with general anaesthesia can exaggerate these haemodynamic changes. This study compared ISB combined with general anaesthesia, with ISB alone, in 29 patients undergoing elective shoulder surgery. Heart rate and oxygen saturation remained stable th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…We take this as evidence that the observed hypotension was related to setting the patient in the semi-upright position soon after the induction dose of propofol [6], since most treatment events were triggered by a decrease of systolic blood pressure after induction of anaesthesia. In a similar, smaller study on younger patients, in which all patients had an ISB while one group had an additional general anaesthetic, Ozzeybek et al found that the combination of the two techniques caused a significantly greater decrease in arterial blood pressure than the ISB alone [9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We take this as evidence that the observed hypotension was related to setting the patient in the semi-upright position soon after the induction dose of propofol [6], since most treatment events were triggered by a decrease of systolic blood pressure after induction of anaesthesia. In a similar, smaller study on younger patients, in which all patients had an ISB while one group had an additional general anaesthetic, Ozzeybek et al found that the combination of the two techniques caused a significantly greater decrease in arterial blood pressure than the ISB alone [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Such a difference that persists past the duration of action of mepivacaine could be evidence of a pre-emptive effect of the regional anaesthesia [4]. Ozzeybek et al [9] studied the course of postoperative pain severity in patients undergoing shoulder surgery under general anaesthesia with ISB. However, since the authors failed to give the actual pain scores, it is not possible to compare their results with those in our corresponding GA-ISB group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic hemodynamic parameters are not affected in the blockade of peripheral nerves of upper extremity [3,[24][25][26]. Therefore, they are important in balanced anesthetic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moving into an upright position activates the sympathetic nervous system, resulting in an increase in the systemic vascular resistance (SVR) and the systemic BP and a reduction in the cardiac output (CO) [11]. In contrast, the upper extremity mABP and SctO 2 values are significantly decreased when the position of an anesthetized patient is changed to the BCP [8] [9] [10] [12]. It has been suggested that the hydrostatic pressure gradient between the brain and the upper extremities plays a role in the decrease in the brain BP that is observed when anesthetized patients are placed into the BCP and that the SctO 2 value decreases due to cerebral hypoperfusion [8] [9].…”
Section: Introductionmentioning
confidence: 99%